Textual and Contextual Studies on Education in Surah Al-Fatihah As the Axis of Life - Nur Hadi; Ali Mahfuz Munawar (Journal of Islamic Studies and Education, 2023)
The text is an expression of words that are genuinely unchangeable in their alternative meaning. Additionally, the term "text" also refers to a manuscript or document that holds a sacred meaning. In the context of socio-historical circumstances during the codification of the Qur'an and the reader's circumstances, this article examines the values of Islamic education found in Surah Al-Fatihah. The collected data is then analyzed using the tahlily method, comparison, and interpretation. The results of this study indicate that there are values of Islamic education present in Surah Al-Fatihah. Firstly, there is the value of faith education, which includes faith in God through His grace, faith in God through the unity of His deeds, faith in God through His grace (ar-rahman and ar-rahim), and faith in the last day (retaliation). Secondly, there is the value of worship education in a broad sense. Thirdly, there is the value of sharia education in a broad sense. Fourthly, there is the educational value of the story. There is a very close relevance between the values of Islamic education and Islamic education itself. Specifically, the value of faith serves as the basis for Islamic education, covering all components of education, including educational goals, the educational curriculum, methods of education, and educational evaluation.